Limited knowledge, low risk awareness, and eating out are associated with higher sugar-sweetened beverage consumption among adults aged 18–64 in Beijing - Liyu Huang; Yiran Li; Yingjie Yu; Yan Zhang; Bo Yu; Xinyue Guo; Hairong He; Jiali Duan (PLoS ONE, 2025)
Objectives The purpose of this study was to analyze the prevalence of sugar-sweetened beverage (SSB) consumption among residents aged 18–64 in Beijing and to identify associated influencing factors. Methods A cross-section study was conducted from June 1,2024 to May 31, 2025, including 10,409 residents aged 18–64 in Beijing. Logistic regression was applied to examine demographic, behavioral, and knowledge-related factors associated SSB consumption. Results The overall prevalence of SSB consumption was 38.7%. After adjusting for demographic factors, infrequent checking nutrition labels when purchasing food (ORs ranging from 1.348 to 1.570), infrequent active weight monitoring (ORs ranging from 1.290 to 1.428), dining out/taking out food >1 day/week (ORs ranging from3.495 to6.692), moderate-intensity physical activity less than 300 minutes a week (ORs ranging from 1.237 to 1.326), lack of knowledge about SSB (ORs ranging from 1.240 to 1.361), and awareness of the health risks of SSB (OR=1.198) were the risk factors for SSB consumption. Conclusions SSB consumption among Beijing adults remains high. Men, urban residents, and younger adults represent priority groups for intervention. Strengthening nutrition education, improving health literacy, and promoting healthier dietary behaviors are essential strategies to reduce SSB consumption and improve population health.